2013
DOI: 10.1111/evj.12049
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of midazolam after intravenous administration to horses

Abstract: Midazolam produces muscle relaxation but not sedation in adult horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…Hubbell et al. () report a median t 1/2β for midazolam of 3.6 hours (range 2.0–4.1) after an IV dose of 0.05 mg kg −1 in conscious healthy horses. Muir et al.…”
Section: Introductionsupporting
confidence: 91%
“…Hubbell et al. () report a median t 1/2β for midazolam of 3.6 hours (range 2.0–4.1) after an IV dose of 0.05 mg kg −1 in conscious healthy horses. Muir et al.…”
Section: Introductionsupporting
confidence: 91%
“…However, whilst benzodiazepines are routinely used in equine anaesthesia for these effects there are few studies demonstrating the benefits of including them in a ketamine-alpha-2 agonist induction protocol [8][9][10]. Ataxia and weakness secondary to muscle relaxation caused by benzodiazepines have also been reported by others [8,14,16,17], however no difference in recovery quality or degree of ataxia was observed in this study. Marntell and Nyman [9] reported that the use of diazepam improved muscle relaxation and these findings are consistent with this study and others [10].…”
Section: Discussionmentioning
confidence: 45%
“…The effects of benzodiazepines on muscle relaxation are well known [4] and have been demonstrated for midazolam in many domestic species [12][13][14][15]. The effects of benzodiazepines on muscle relaxation are well known [4] and have been demonstrated for midazolam in many domestic species [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potentially, the lack of midazolam or diazepam in these horses may have contributed to the speed and smoothness of recovery. Midazolam has a long half-life in horses; greater than 200 minutes at 0.05 mg/kg intravenous and greater than 400 minutes at 0.1 mg/kg intravenous (Hubbell and others 2013). Although there is limited pharmacokinetic reported for propofol in horses, the half-life of propofol when administered with ketamine is 69 minutes (Nolan and others 1996).…”
Section: Discussionmentioning
confidence: 99%